Answer:
g = 29/26
Step-by-step explanation:
Subtract the right side and simplify:
5g +4(-7 +5g) -(1 -g) = 0
5g -28 +20g -1 +g = 0 . . . . . . eliminate parentheses
26g -29 = 0 . . . . . . . . . . . . . . collect terms
g -29/26 = 0 . . . . . . . . . . . . . divide by the coefficient of x
g = 29/26 . . . . . . . . . . . . . . . . add the opposite of the constant
_____
Check
5(29/26) +4(-7+5(29/26)) = 1 -(29/26)
145/26 + 4(-7 +145/26) = -3/26
145/26 +4(-37/26) = -3/26
(145 -148)/26 = -3/26 . . . . . . . . true; answer checks OK